The impact of total sleep deprivation upon supine and head up tilt hemodynamics using non-linear analysis in firefighters. (September 2021) - Kujawski, Sławomir; Buszko, Katarzyna; Cudnoch-Jędrzejewska, Agnieszka; Słomko, Joanna; Jakovljevic, Djordje G.; Newton, Julia L.; Zalewski, Paweł
Highlights: The impact of 31h of TSD on cardiovascular autonomic modulation was examined. Entropy analysis was conducted using Permutation, Amplitude Aware Permutation. TSD alters ANS function indicators in supine and response to orthostatic stress. TSD alters cardiac and both spectral and entropy analysis of blood pressure when supine. Results of spectral and PE analysis of BP in response to HUT were changed after TSD. Abstract: Purpose: The impact of 31 h of total sleep deprivation (TSD) on cardiovascular autonomic modulation was evaluated in 46 volunteers all professional fire brigade units officers (all men, mean age = 32.11 ± 6.4). Methods: Hemodynamic examination was obtained at baseline and after 31 h of Total Sleep Deprivation (TSD). Each measurement period included supine and head-up tilt (HUT) test response. Continuous beat-to-beat systolic blood pressure (sBP), diastolic blood pressure (dBP) and mean blood pressure (mBP), heart rate (HR), stroke volume (SV), left ventricular ejection time (LVET) and cardiac output (CO) were calculated in rest supine position and in response to HUT. Nonlinear analyses were conducted using Permutation Entropy (PE), Amplitude Aware Permutation Entropy (AAPE) and Fractal Dimension (FD). Results: Supine increase of HR and decrease in RRI, LVET and entropy of LVET were observed after 31-h of TSD. Increase in entropy of mBP was indicated by AAPE and PE methods. Response to HUT, values of spectral analysis of blood pressure (normalized units of high frequency of sBP and dBP) was altered. Permutation entropy of mBP in response to HUT were significantly changed after 31-h of TSD. Conclusions: TSD alters autonomic nervous system modulation of cardiac and vascular functioning while supine and in response to orthostatic stress. TSD resulted in changes in cardiac and both spectral and two methods of analysis of entropy of blood pressure when supine. Values of spectral analysis of blood pressure and permutation entropy of mean blood pressure in response to HUT were significantly changed after 31 h of TSD.